Size Distribution, Length-Weight Relationship, and Size at Morphometric Maturity of the Mud Spiny Lobster Panulirus polyphagus (Herbst, 1793) in the Johor Strait - Waiho, Khor; Fazhan, Hanafiah; Shu-Chien, Alexander Chong; Abualreesh, Muyassar H.; Ma, Hongyu; Syahnon, Mohammad; Azmie, Ghazali; Razman, Nurul Jannah; Ikhwanuddin, Mhd (Frontiers in Marine Science, 2021)
Spiny lobsters of the genus Panulirus are economically important and support local fishing communities. However, mud spiny lobster Panulirus polyphagus is among the least known species within this genus in terms of their biological information. This study relates to the size distribution, length-weight relationship, and size at morphometric maturity of P. polyphagus in the Johor Strait. Within the year 2010, 300 specimens were collected off the coast of Johor Strait, Malaysia. There was no significant difference in body size (carapace length, CL) and body weight (BW) between sexes. CL and BW was highly correlated and males of P. polyphagus displayed positive growth allometry whereas the opposite was observed in females. On the basis of merus (ML) and carpus length (CPL) of the third right walking leg, piecewise linear regression analysis estimated the size at maturity for male was 6.58 cm CL (based on ML) and 7.58 cm CL (based on CPL), whereas it was 8.18 cm CL (based on ML) and 6.75 cm (based on CPL) for females. Two discriminant functions of high classification and re-validation rates (> 98.6% in males, > 98.7% in females) that can discern maturation status in males and females of P. polyphagus were derived using discriminant function analysis. Biological information derived from this study serves as an essential baseline for future fishery management and conservation of P. polyphagus.